Assessing the Impact of Tourism on Country Brand Value - KÁLMÁN, Botond Géza; ZÉMAN, Zoltán; MALATYINSZKI, Szilárd (Journal of Ecohumanism, 2024)
This research explores the connection between tourism statistics and country brand value, as well as the impact tourism has on it, by utilizing public data sources and employing statistical techniques. A country’s brand reflects its image as perceived by foreign audiences, representing the nation’s reputation and standing internationally. This perception is mirrored in the influx of tourists visiting the country. While brand value is typically not measured by the number of arrivals, but rather by the country’s tourism image, prior studies have shown that higher brand value leads to an increase in foreign visitors. However, fewer investigations have focused on whether the volume of tourists directly influences the country’s brand value. The findings of this study demonstrate a significant link between the two, revealing a causal relationship. Nevertheless, there is some uncertainty surrounding the causality, which future research aims to clarify. The goal of this preliminary study was to explore whether this question could be effectively addressed.